EFEKTIVITAS HEALTH VIDEO EDUCATION TERHADAP LIFE STYLE PADA PASIEN BATU GINJAL DI RUANG POLI UROLOGI RSU KOTA TANGERANG SELATAN - Andriati, Riris; Purwadiansyah, Anggie Ellen; Pratiwi, Rita Dwi (Edu Masda Journal, 2025)
ABSTRACTAccording to the World Health Organization (WHO) in 2021, the prevalence and recurrence rate of kidney stones is increasing, affecting about 12% of the population worldwide. The incidence is estimated to reach 600,000 sufferers between the ages of 20 and 49 years. Based on data from the Ministry of Health of the Republic of Indonesia on World Kidney Day in 2019, the number of kidney stone sufferers in Indonesia is 1,499,400 people with a prevalence of 6% (Ministry of Health of the Republic of Indonesia, 2019). The purpose of this study was to determine the effectiveness of health video education on life style in kidney stone patients. The research method with a quantitative study approach and a quasi-experimental research design with a pre and post test design consisting of one group, namely the group that was given health video education treatment on life style in kidney stone patients. Data collected by questionnaire. The number of samples was 98 respondents at the Urology Poly of the South Tangerang City Hospital. The results of the study obtained before the intervention (pre-test) that 62 respondents (63.2%) showed a sufficient life style and 2 respondents (2.04%) showed a very good life style. Meanwhile, after the intervention (post-test), 76 respondents (77.5%) showed a very good improvement in life style and 22 respondents (22.4%) showed a good increase in life style. The results of the statistical test using the Wilcoxon test were obtained p-value = 0.000 < a 0.05, so it can be concluded that there is an effectiveness of health video education on life style in kidney stone patients in the Urology Polyclinic room of South Tangerang City Hospital.                                              ABSTRAKMenurut World Health Organization (WHO) tahun 2021, revalensi dan tingkat kekambuhan batu ginjal semakin meningkat, dengan mempengaruhi sekitar 12% populasi di seluruh dunia. Insidennya diperkirakan mencapai 600.000 penderita diantara usia 20 hingga 49 tahun. Berdasarkan hasil data Kementerian Kesehatan Republik Indonesia pada Hari Ginjal Sedunia tahun 2019, jumlah penderita batu ginjal di Indonesia sebanyak 1.499.400 orang dengan prevalensi sebesar 6% (Kemenkes RI, 2019). Tujuan penelitian ini adalah untuk mengetahui efektivitas health video education terhadap life style pada pasien batu ginjal. Metode penelitian dengan pendekatan study kuantitatif dan design penelitian quasi eksperiment dengan rancangan one grup pre and post test design yang terdiri atas satu kelompok, yaitu kelompok yang diberi perlakuan health video education terhadap life style pada pasien batu ginjal. Data yang dikumpulkan dengan cara kuesioner. Jumlah sampel sebanyak 98 responden di Poli Urologi RSU Kota Tangerang Selatan. Hasil penelitian diperoleh sebelum intervensi (pre-test) bahwa 62 responden (63,2%) menunjukan life style cukup dan 2 responden (2,04%) menunjukkan life style sangat baik. Sedangkan setelah dilakukan intervensi (post-test) bahwa 76 responden (77,5%) menunjukkan peningkatan life style yang sangat baik dan 22 responden (22,4%) menunjukkan peningkatan life style yang baik. Hasil uji statistik menggunakan uji Wilcoxon diperoleh p-value = 0,000 < a 0,05 maka dapat disimpulkan bahwa terdapat efektivitas health video education terhadap life style pada pasien batu ginjal di ruang Poli Urologi RSU Kota Tangerang Selatan.